Politics of the All-India Muslim League, 1924-1940 - Kishwar Sultana (Karachi Oxford University Press, 2016)
This book outlines a narrative account of Jinnahs role in the political development of the Muslim League during the years 1924-1940. This period remains of crucial importance for understanding the achievement of Pakistan. While most studies have focused on the closing stages of the freedom movement this book reveals Jinnahs important influence in the reorganization of the Muslim League throughout a period when it faced major challenges to establish its political importance. The narrative draws on new sources in order to challenge some of the interpretations of key developments such as the 1937 Jinnah-Sikander Pact and to draw out the significance of Jinnahs role in the organization of the Muslim League. It discusses the evolution of the All-India Muslim League through the years from its birth to the Pakistan Resolution in 1940 and is useful in understanding the development of the League in the closing decades of British rule.
Include Appendices, Bibliography and Index.
Keywords: Muslims--Political activity -- India -- Politics and government -- All-India Muslim League